2019
DOI: 10.1097/spv.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Self-Management Gellhorn Pessary for Symptomatic Pelvic Organ Prolapse

Abstract: Objective The aim of this study is to estimate the long-term survival and to identify adverse events associated with the use of Gellhorn pessaries over a 9-year period. Methods This was a retrospective case series study at a tertiary urogynecology unit in Taiwan. Between January 2009 and June 2017, 93 patients who opted for self-management Gellhorn pessaries to treat symptomatic pelvic organ prolapse (POP) and who were continuously followed-up were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In a study examining 289 women fitted with ring pessaries for symptomatic POP, Manonai et al found that only 61.7% were still using them 5 years later and that self-care was the only significant factor that was predictive of continued compliance for 3 years [ 15 ]. In a study of 93 patients who opted for self-management of Gellhorn pessaries to treat symptomatic POP, Chien et al found that only 47.2% of the study participants were still using their pessaries after 5 years [ 16 ]. Our relatively high continuation rate in the present study (82.2%) compared with those reported previously could be attributed, at least in part, to the use of a different type of pessary.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining 289 women fitted with ring pessaries for symptomatic POP, Manonai et al found that only 61.7% were still using them 5 years later and that self-care was the only significant factor that was predictive of continued compliance for 3 years [ 15 ]. In a study of 93 patients who opted for self-management of Gellhorn pessaries to treat symptomatic POP, Chien et al found that only 47.2% of the study participants were still using their pessaries after 5 years [ 16 ]. Our relatively high continuation rate in the present study (82.2%) compared with those reported previously could be attributed, at least in part, to the use of a different type of pessary.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies provided data on risk of adverse events with long-term pessary use (without removal or cleaning) [17][18][19][20][21][22][23]. Nine additional articles were reviewed that provided information of interest during the pandemic [24][25][26][27][28][29][30][31][32].…”
Section: Pessary Managementmentioning
confidence: 99%
“…Based on review of the literature (16 studies) and expert consensus: [16]. Use of a specific telemedicine encounter is preferred for tracking and reimbursement purposes over a telephone encounter (typically used for sharing of discrete information) & Patients can safely extend the time interval between pessary cleanings to 6 months (and, in some cases, up to 24 months) with minimal risk of adverse events [17][18][19][20][21][22][23]. & Patients capable of pessary removal and reinsertion should be encouraged to self-clean their pessary [27,[31][32][33][34][35].…”
Section: Pessary Managementmentioning
confidence: 99%
“…Seven studies provided data on risk of adverse events with long-term pessary use (without removal or cleaning) [17][18][19][20][21][22][23]. Nine additional articles were reviewed that provided information of interest during the pandemic [24][25][26][27][28][29][30][31][32].…”
Section: Pessary Managementmentioning
confidence: 99%
“…& Patients can safely extend the time interval between pessary cleanings to 6 months (and, in some cases, up to 24 months) with minimal risk of adverse events [17][18][19][20][21][22][23]. & Patients capable of pessary removal and reinsertion should be encouraged to self-clean their pessary [27,[31][32][33][34][35].…”
Section: Pessary Managementmentioning
confidence: 99%